Assessment of Cerdocyon thous distribution in an agricultural mosaic, southeastern Brazil - Micchi de Barros Ferraz, Katia Maria Paschoaletto; de Siqueira, Marinez Ferreira; Martin, Paula Sanches; Esteves, Carolina Franco [UNESP]; Zarate do Couto, Hilton Thadeu (Walter de Gruyter & Co, 2010)
Crab-eating fox, Cerdocyon thous, is a habitat generalist species relatively common throughout its range inhabiting most environments owing to its low habitat requirements. Because no information is available for anthropogenic habitats, this study aimed to describe the species occurrence in a highly fragmented and heterogeneous landscape in southeastern Brazil. C. thous was surveyed in 95 study sites in four main land covers (native forest, eucalyptus forest, sugar cane and pasture) from April to September 2006. Presence records (n=28) and landscape variables (land cover, heterogeneity, stream and forest fragment distance, elevation and slope) were used for modeling in Maxent. The bootstrapping method was used for sampling 70% of the dataset for training and 30% for testing models. The species was equally distributed in all types of land cover, although it was more frequent in the sugar cane areas and more associated with forest fragments and heterogeneous habitats. The potential distribution model predicted forest patches and its surroundings as highly suitable for the species. It also predicted part of the sugar cane matrix as highly suitable, probably related to prey availability. Results suggested that the anthropogenic landscape studied encompasses many suitable habitats for species occurrence, resulting in the necessity to assess its potential role in vertebrate communities.
Keywords: agroecosystem; habitat generalist species; Maxent; potential distribution; track survey